The Efficiency of Voltage Stabilizer Installation in Addressing Power Quality Issues through Analysis Using an Injection Power Analyzer in the Manufacturing Industry of PT XYZ - Varin Pasaribu; Faiz Husnayain (Universitas Indonesia, 2026)
In today's modern era, electrical energy has become a vital secondary need for society and serves as a key foundation for economic development. Along with the rapid advancement of complex electronic devices, various power quality disturbances have emerged, negatively impacting industrial equipment such as active line modules and motor drivers, potentially disrupting production processes. A similar issue occurred at PT XYZ, prompting real-time power quality monitoring using a power analyzer installed on the LVMDB panel. This device can record and analyze power quality trends visually. Based on the data, PT XYZ took corrective actions, including adjusting the tap changer position from 3 to 1 and installing a voltage stabilizer, which effectively stabilized the voltage supplied to production machines. Furthermore, a harmonic analysis simulation showed a Total Harmonic Distortion of 8,35% for current and 7,92% for voltage. After applying a power filter design in ETAP, these values significantly decreased to 1.98% (current) and 2.08% (voltage). Based on these findings, it is recommended that PT XYZ proceed with the installation of a power filter to comprehensively improve power quality.